INDONESIAN PREPOSITIONAL PHRASES IN THE SHORT STORY HYANG IBU BY MADE ADNYANA OLE - Ni Luh Gede Liswahyuningsih; I Wayan Dede Putra Wiguna; Kadek Windari; I Wayan Agus Sukmadana; Ni Komang Sabina Sanji Putri (Program Studi Pendidikan Bahasa Indonesia dan Daerah Universitas PGRI Mahadewa Indonesia, 2023)
This study aims to determine the syntactical and functional structure of Indonesian prepositional phrases in the short story